Consequences of the crosstalk between monocytes/macrophages and natural killer cells - Michel, Tatiana; Hentges, François; Zimmer, Jacques (Frontiers in Immunology, 2013)
The interaction between NK cells and different other immune cells like T cells and dendritic cells is well described, but the crosstalk with monocytes or macrophages and the nature of ligands/receptors implicated are just emerging. The macrophage-NK interaction is a major first-line defense against pathogens (bacteria, viruses, fungi and parasites). The recruitment and the activation of NK cells to perform cytotoxicity or produce cytokines at the sites of inflammation are important to fight infections. The two main mechanisms by which macrophages can prime NK cells are (i) activation through soluble mediators such as IL-12, IL-18 and (ii) stimulation through direct cell-to-cell contact. We will discuss the progress in matters of modulation of NK cell functions by monocytes and macrophages, in the steady state and during diseases.